2018
DOI: 10.1016/bs.acdb.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Social Influence on Positive Youth Development: A Developmental Neuroscience Perspective

Abstract: Susceptibility to social influence is associated with a host of negative outcomes during adolescence. However, emerging evidence implicates the role of peers and parents in adolescents' positive and adaptive adjustment. Hence, in this chapter we highlight social influence as an opportunity for promoting social adjustment, which can redirect negative trajectories and help adolescents thrive. We discuss influential models about the processes underlying social influence, with a particular emphasis on internalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 159 publications
(215 reference statements)
6
109
0
4
Order By: Relevance
“…Thus, caregivers may promote recruitment of mPFC to downregulate affective processing of the amygdala in order to regulate their inhibition within socially appetitive contexts. Our findings are consistent with theories suggesting that adolescence is a period of neurobiological flexibility and potential (Crone & Dahl, ; Telzer et al., ), such that neural plasticity in the adolescent brain is amenable to caregivers’ influence for modulating neural activation and regulation. The neuroimaging analyses provide novel, but low powered, findings, which should be interpreted with caution and utilized to propel future work investigating the neurobiological underpinnings of maternal buffering during adolescence.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, caregivers may promote recruitment of mPFC to downregulate affective processing of the amygdala in order to regulate their inhibition within socially appetitive contexts. Our findings are consistent with theories suggesting that adolescence is a period of neurobiological flexibility and potential (Crone & Dahl, ; Telzer et al., ), such that neural plasticity in the adolescent brain is amenable to caregivers’ influence for modulating neural activation and regulation. The neuroimaging analyses provide novel, but low powered, findings, which should be interpreted with caution and utilized to propel future work investigating the neurobiological underpinnings of maternal buffering during adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…Older adolescents performed significantly worse in response to socially appetitive stimuli compared to socially aversive stimuli, whereas younger participants did not demonstrate this disparity. These findings are consistent with developmental theory suggesting that adolescents are neurobiologically sensitive to positive social cues to help them obtain social status and navigate novel social environments (Kuhn, 2006;Telzer et al, 2018), as well as empirical work indicating that adolescents experience disinhibition in socially appetitive contexts (Perino et al, 2016;Somerville et al, 2011). While adolescents were more susceptible to disinhibition to appetitive stimuli, we found that this emotional dysregulation was completely buffered in the presence of their mothers.…”
Section: Figuresupporting
confidence: 90%
See 1 more Smart Citation
“…If individuals do not perceive their neighbourhoods as disadvantaged, neighbourhoods with objectively disadvantageous structural characteristics may not be associated with a higher risk for depression. Adolescents and young adults may be less likely to perceive their neighbourhoods as disadvantaged than older individuals, even in the presence of objective indicators, if their peers in similar neighbourhoods also do not perceive their neighbourhoods as disadvantaged 53. Alternatively, supportive relationships with peers may buffer the stressors associated with neighbourhood adversity that are implicated in the aetiology of depression 53…”
Section: Discussionmentioning
confidence: 99%
“…Se prueba a sí mismo, una y otra vez, para ver de lo que es capaz y lo que necesita para sentirse igual a sus pares (1) . Además, en esta etapa, los cambios biológicos, sociales y psicológicos replantean la definición personal y social del adolescente por medio de una segunda individuación que movilice procesos de exploración, diferenciación del medio familiar, búsqueda de pertenencia y sentido de vida, además de otras situaciones que conllevan ansiedad y vulnerabilidad (2,3) .…”
Section: Introductionunclassified